Prinsip-Prinsip Komunikasi dalam Hadits Nabi SAW - Bahrudin, Bahrudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
Communication is requirement of the human being. Everyone could not life without it. Neverthelles it has constructed healthy. Therefore. the prophet Muhammad trough hadits ordered the all moslems about it (healthy communication with whoever). Among others, he ordered them to be honest, to use a good language and to use an appropriate diction in the communication process. He forbade hardly all unhealthy communication patterns. Becouse its able to demage communication partners.